so 2 x 32 is 64
u need to find factors of 64 that add or subtract to 16, this one's easy, its 8 and 8
so
2x^2 +8x + 8x + 32 ( factor each half of the expression)
2x( x + 4) + 8(x + 4) Then you eliminate the "(x+4)" in your head to come up with the partner factor of " 2x+8"
so...
(2x + 8)(x+4)
then u still have to factor the first one,
2(x+4)(x+4)
or
2(x+4)^2
EDIT:
I triple checked this, my answer IS RIGHT, the guys below me left some steps out
2007-06-12 10:54:20
·
answer #1
·
answered by sellasell 3
·
1⤊
3⤋
You can figure out factoring by finding the multiples of the first and last number, and seeing whnich combination adds to sixteen. For example: the only two factors of 2 are 1, and 2. However, 32, has a number of multiples, such as 4 and 8; 16 and 2, etc. (It's sort of hard to explain, maybe trying looking up the scissor method for factoring.) Anyway, it factors to: (2x+8)(x+4). And the first factor can be broken down even further so the complete answer would be: 2(x+4)(x+4) or 2(x+4)^2.
2007-06-12 11:00:08
·
answer #2
·
answered by Sarah W 3
·
0⤊
1⤋
2x^2 + 16x + 32
= 2(x^2+8x+16)
= 2 (x+4)^2
2007-06-12 10:56:19
·
answer #3
·
answered by ironduke8159 7
·
0⤊
1⤋
Use AC method of factor.
Find two numbers that multiply to AC and add to B
2x^2 + 16x + 32
take out 2
2 (x^2 + 8x + 16)
find two numbers that multiply to 16 and add to 8
the two numbers are 4 and 4
since the leading coefficient is 1 after take out the 2. Plug the two numbers in factor form
2 (x + 4) (x + 4)
or
2(x+4)^2
2007-06-12 10:58:10
·
answer #4
·
answered by 7
·
0⤊
1⤋
2x^2 + 16x + 32
Your first step is to factor out the greatest common monomial; in this case, it's a constant, 2.
2(x^2 + 8x + 16)
Now factor as per usual methods.
2(x + 4)(x + 4)
or, quite simply,
2(x + 4)^2
2007-06-12 10:57:41
·
answer #5
·
answered by Puggy 7
·
0⤊
1⤋
2(x + 4)^2
2007-06-12 12:34:07
·
answer #6
·
answered by UNIQUE 3
·
0⤊
0⤋
= 2.(x² + 8x + 16)
= 2.(x + 4).(x + 4)
= 2.(x + 4)²
2007-06-12 21:49:01
·
answer #7
·
answered by Como 7
·
0⤊
0⤋
2x^2 + 16x + 32
= 2(x^2 + 8x + 16)
= 2(x + 4)^2
= 2(x+4)(x+4)
===============================================
For more assistance please visit www.classof1.com.
Classof1 - leading web tutoring and homework help.
Toll free - 1877-252-7763
2007-06-12 10:58:20
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
first put 2 in evidence:
2(x^2 + 8x + 16)
Now you find the roots of the function into parenthesis: x=-4 or x=-4 double root
2(x+4)(x+4) = 2(x+4)^2 OK!
2007-06-12 10:59:47
·
answer #9
·
answered by vahucel 6
·
0⤊
1⤋
2(x^2+8x+16) => 2(x+4)^2
2007-06-12 10:57:12
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋